Polydopamine-Derived Carbon: What a Critical Role for Lithium Storage? - Qian, Xiaoyong; Zhang, Fangzhou; Zhao, Yuye; Liang, Kai; Luo, Wei; Yang, Jianping (Frontiers in Energy Research, 2020)
Polydopamine-derived carbon materials have attracted tremendous attention owing to nitrogen heteroatom doping. However, it is challenging to estimate the effect of the morphology and porosity of the polydopamine-derived carbon for lithium storage. Here, we designed three polydopamine-derived carbon materials with different morphologies and porosity: carbon nanospheres (CNs), mesoporous carbon nanospheres (MCNs), and bowl-like mesoporous carbon nanoparticles (BMCNs) to evaluate the electrochemical performance. Such a bowl-like mesoporous structure combines multiple advantageous features, including mesoporous channels and shorter transmission distance, thus delivering a high specific capacity. In addition, our work provides new insight into the electrochemical performance of polydopamine-derived carbon and a useful reference for its future application in high-performance lithium ion battery (LIB) electrode materials.